Kriminalisasi Korban Kekerasan Seksual melalui Delik Pencemaran Nama Baik: Urgensi Klausul Anti-SLAPP dalam Implementasi UU TPKS - Maliki Sirojudin Agani (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
The issue of criminalizing victims of sexual violence through the use of defamation charges is gaining public attention because it is often used to silence victims who try to share their experiences. This article describes how defamation provisions in the Criminal Code and the Electronic Information and Transactions Law are often used as instruments of Strategic Lawsuits Against Public Participation (SLAPP) directed at victims, making victims even more vulnerable. The study uses a normative approach to assess the effectiveness of legal protection in the Sexual Violence Criminal Law (TPKS Law). The results of the analysis show that the TPKS Law does not explicitly include an anti-SLAPP mechanism, leaving open the possibility for the reported party to file a counter-report against the victim. Studies of the SPI, KPI, and Baiq Nuril cases show a recurring pattern, namely the use of defamation articles as a means of silencing victims and slowing down the process of exposing sexual violence. This article proposes an anti-SLAPP clause based on a progressive interpretation of the anti-revictimization principle in the TPKS Law. This proposal is reinforced by the push for the application of an early dismissal mechanism for reports that show strong indications of intimidation, so that victims receive maximum protection in the legal process.